Practice standard for project risk management (Project Management Institute, 2009)
Presents an introduction to the processes of risk management, discussing how to identify and quantify risks in the business cycle, monitor and control them, and plan for various responses.
"This practice standard is consistent with A guide to the Project Management Body of Knowledge (PMBOK® Guide 4th Edition)"--Page 4 of cover
Title from title screen.
"PMI global standard"--Thumbnail image of cover
Keywords: Risk management -- Standards.; Project management -- Standards.; elektronické knihy; electronic books